Molecular tracking of insulin resistance and inflammation development on visceral adipose tissue - Bensussen, Antonio; Torres-Magallanes, José Antonio; Roces de Álvarez-Buylla, Elena (Frontiers in Immunology, 2023)
Background Visceral adipose tissue (VAT) is one of the most important sources of proinflammatory molecules in obese people and it conditions the appearance of insulin resistance and diabetes. Thus, understanding the synergies between adipocytes and VAT-resident immune cells is essential for the treatment of insulin resistance and diabetes. Methods We collected information available on databases and specialized literature to construct regulatory networks of VAT resident cells, such as adipocytes, CD4+ T lymphocytes and macrophages. These networks were used to build stochastic models based on Markov chains to visualize phenotypic changes on VAT resident cells under several physiological contexts, including obesity and diabetes mellitus. Results Stochastic models showed that in lean people, insulin produces inflammation in adipocytes as a homeostatic mechanism to downregulate glucose intake. However, when the VAT tolerance to inflammation is exceeded, adipocytes lose insulin sensitivity according to severity of the inflammatory condition. Molecularly, insulin resistance is initiated by inflammatory pathways and sustained by intracellular ceramide signaling. Furthermore, our data show that insulin resistance potentiates the effector response of immune cells, which suggests its role in the mechanism of nutrient redirection. Finally, our models show that insulin resistance cannot be inhibited by anti-inflammatory therapies alone. Conclusion Insulin resistance controls adipocyte glucose intake under homeostatic conditions. However, metabolic alterations such as obesity, enhances insulin resistance in adipocytes, redirecting nutrients to immune cells, permanently sustaining local inflammation in the VAT.